Assessment of integrated community case management of childhood illness (ICCM) practices by trained patent and proprietary medicine vendors (PPMVs) in Ebonyi and Kaduna states, Nigeria - Akpu Blessing Oko; Anyanti Jennifer; Adizue Jane Chinyere; Nwankwo Jehosephat Nelson; Idogho Omokhudu; Onyezobi Chinedu Edward; Aizobu Dennis (BMC, 2023)
Abstract Introduction An Integrated Community treatment of Childhood disease (ICCM)- focused intervention involving a large number of Patent and proprietary medicine vendors (PPMVs) was conducted by Society for Family Health Nigeria to improve management of childhood, malaria, pneumonia and diarrhea with an intervention approach focused on knowledge and skill improvement. The intervention was conducted in Kaduna and Ebonyi state; recruited and trained 15 interpersonal communication agents (IPCAs) who were saddled with the responsibility to sensitize and mobilize caregivers with children within the age bracket of 2 months to 5 years to our mapped PPMVs within the communities, on the account of Malaria, Diarrhea, and Pneumonia; while the IPCAs in return monitor the quality-of-service delivery. Following the intervention, the Society for Family health conducted a study to demonstrate the effectiveness of interventions such as ICCM training, supervision and linkage to quality ICCM commodities, among PPMVs to achieve high levels of knowledge and performance in diagnosing and treating common childhood illnesses. Methods Longitudinal research (before and after study) was adopted for the study. From the 387 PPMVs recruited and trained by SFH, 165 PPMVs were systematically selected to participate in the study, before and after the implementation of the intervention. Using SPSS version 22, data from the observation and completed questionnaires were analyzed and a chi-square test was used to examine the associations between the categorical information collected prior and after the intervention. The analysis was conducted at 5% level of significance. Results More than 50 % of the study participants were females (56.4%) and majority were either Junior community extension workers (35%) or Senior community extension worker (27%). About 21.8% trained PPMVs could not appropriately treat malaria in the first quarter of the intervention, however, there was a significant decrease to 1.8% in second quarter in the number of those that cannot appropriately diagnose and treat malaria. There was also a decrease in the number of those who could not treat cough and fast breathing from 47(28.5%) to 14(8.5%) in the second quarter and for diarrhea from 33.3% in the first quarter to 2.4% in the second quarter. Conclusion The study revealed a significant improvement in the quality of treatment provided by the trained PPMVs across the three disease areas. PPMVs in hard-to-reach areas should be trained and supported to continuously provide quality services to change the indices of under-5 mortality in Nigeria.